PENGARUH LINGKUNGAN KELUARGA TERHADAP PRESTASI BELAJAR SISWA DI SEKOLAH DASAR NEGERI TUNGGAKJATI IV KARAWANG JAWA BARAT - Suandi Silalahi, Tamimi, Mustakim, (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to examine the influence of family environment on students' academic achievement in Grade IV at SDN Tunggakjati IV Karawang, West Java. The research employs a quantitative method with data collection techniques including questionnaires and documentation. The study sample consists of 13 students and their parents. Data on the family environment were obtained through a questionnaire comprising 15 statements related to parenting styles, home atmosphere, and parental supervision of children’s education. Students' academic achievement was measured based on the average grades from their report cards. The data analysis results show a calculated r-value of 0.837, which is higher than the critical r-value at a 5% significance level (0.553). This indicates a significant influence of the family environment on students' academic achievement. A supportive family environment, such as parental attention, a comfortable home atmosphere, and emotional support, contributes positively to academic performance. Conversely, a less supportive family environment negatively impacts students' learning outcomes. These findings align with theories proposed by Slameto (2010) and Siswono (2007), which state that the family is a major external factor influencing students' learning processes and outcomes. This study highlights the importance of the family’s role in creating an environment conducive to academic success. In conclusion, the family environment significantly influences students' academic achievement, and parents are encouraged to be more proactive in supporting their children's educational development